INTERMEDIATE PRECISION DETERMINATION AT VALIDATION OF METHODS IN PHARMACY - N. A. Epshtein (Разработка и регистрация лекарственных средств)
Merits and demerits of six ways of an assessment of an intermediate precision (IP) for validation of analytical methods are considered. It is established that only four of them can be recommended for IP assessment, and three - with restrictions Recommendations about use of the considered ways of an assessment of IP are made. It is shown that use of the most widely applied way of an assessment of intermediate precision - on a relative standard deviation of set of results of chemists, can lead to receiving a wrong conclusion about an IP of a method. It is offered the new (most universal) way of an assessment of an intermediate precision, that has perspective of application in pharmacy.